2017
DOI: 10.36876/smjbb.1007
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Review of Relation between Full Moon and Different Aspects of Human Health

Abstract: This review is an attempt to consolidate the earlier studies on this subject and to get a broad based idea if there exists any relationship between full moon and various physiopsycological aspects on human like behavior, sleep cycle, cardiovascular system, endocrine system, birthrate, reproductive system. MethodologyData were collected from review of literatures from various scientific studies conducted so far globally. To meet our objectives, we try to do a study and see what actually occurs in the human body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
(40 reference statements)
0
0
0
Order By: Relevance
“…Several scientific explanations have been given to contradict these beliefs, but these are still prevalent. Various studies have shown that the full moon affects the various aspects of health in a human being [1]. These include the effects on the heart, on sleep, on birth rates and time of delivery, on menstruation, and on psychological aspects and neurological aspects of human health.…”
Section: Various Aspects Of Human Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…Several scientific explanations have been given to contradict these beliefs, but these are still prevalent. Various studies have shown that the full moon affects the various aspects of health in a human being [1]. These include the effects on the heart, on sleep, on birth rates and time of delivery, on menstruation, and on psychological aspects and neurological aspects of human health.…”
Section: Various Aspects Of Human Healthmentioning
confidence: 99%
“…The moon, the closest celestial body to Earth, has several myths around it. These myths have been there for years and have existed across the globe [1]. Superstitions regarding the moon are still prevalent worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations